Splenic embolization for a giant splenic hemangioma in a child: a case report - Woosun Choi; Young Bae Choi (BMC, 2018)
Abstract Background Splenic hemangioma is the most common benign tumor of the spleen. However, it remains a rare medical condition in children. Although the natural course of splenic hemangioma is slow growth, treatment for large splenic hemangiomas has been recommended due to the risk of spontaneous rupture causing life-threating hemorrhage. However, the optimal treatment for splenic hemangioma in children is unclear. Case presentation An 11-year-old girl had an enhancing mass, 61 × 54 × 65 mm in size and numerous daughter nodules throughout the entire spleen on a contrast-enhanced computed tomography scan of the abdomen and angiography. The patient was treated by complete embolization at the distal level of splenic artery, which resulted in total splenic infarction. Treatment-related complications were thrombocytosis and postembolization syndrome, including abdominal pain and, intermittent fever below 39 °C. There were no other serious complications, including bleeding. Conclusion Splenic embolization may be a safe and less invasive intervention for children with a large splenic hemangioma. Further studies are needed to confirm the effectiveness of our approach.